Unraveling the role of ruzigrass in soil K cycling in tropical cropping systems - Volf, Marcelo R.; Crusciol, Carlos A. C. [UNESP]; Kovar, John L.; Rosolem, Ciro A. [UNESP] (Springer Nature, 2023)
The introduction of ruzigrass (Urochloa ruziziensis) in rotation or intercropped with a cash crop may improve K cycling in the cropping system due to the ability of its extensive root system to take up nutrients, including non-exchangeable K (Kne), at greater depths in the soil profile. The present study was carried out with the aim of evaluating K cycling and K-use efficiency in cropping systems that include ruzigrass. Three cropping systems in Central West Brazil were studied for three years in the presence and absence of K fertilization: (i) soybean (Glycine max L. Merr.) in a monocropping system with fallow in the off-season; (ii) soybean in rotation with ruzigrass in the off-season; and (iii) soybean following a ruzigrass pasture grown continuously for 30 months. Varieties representing two soybean maturity groups were used. Cover crops improved the balance of K, therefore, monocrop caused, an average, negative balance of − 199 kg ha−1 of exchangeable K (Ke) in the soil, Kne was an important source of available K even in kaolinitic tropical soils, up to 74% of Kne contribution for monocrop, growing soybean in rotation with ruzigrass avoided fertilizer K loss and improve the use of K from the soil such as the positive balance of 103 kg ha−1 of (Ke). The soybean did not respond to K fertilization when cropped after ruzigrass pasture because the grass cycled Kne and released Ke upon residue mineralization. Potassium cycling was improved when ruzigrass was included in the cropping system. The late maturing soybean cultivar took up 40% more Kne than the early cultivar. As a consequence of the nutrient cycling in the system, soybean did not respond to K when cropped in rotation with ruzigrass, although not applying K fertilizer will deplete soil K. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Crop rotation; Exchangeable K; Glycine max L. Merr; Nonexchangeable K; Nutrient cycling; Urochloa ruziziensis